Glioma characterization based on magnetic resonance imaging: Challenge overview and future perspective - Lijuan Zhang (Glioma, 2020)
Brain imaging has been broadly applied in neuroscience for more than 40 years. A wide range of studies on glioma have been carried out based on structural and functional imaging to characterize tumor malignancy, search for biomarker, aid the therapeutic process, and predict the prognosis. As the mainstay of modern neuroimaging, magnetic resonance imaging provides superior resolution and multiple contrasts capturing the morphological, vascular, metabolic, and functional properties of glioma. Furthermore, the development of connectivity-based approach and network models innovates our understanding of glioma in terms of functional remodeling and plasticity at various levels. The focus of this presentation is to overview the challenges of glioma characterization based on conventional magnetic resonance imaging and the future perspective of incorporating connectivity-based approaches into the disease management of glioma.